PSYCHOLINGUISTIC PECULIARITIES OF UNDERSTANDING THE GRAMMATICAL MEANING OF PHRASES AND ITS USE IN SPEECH OF THE SENIOR PRESCHOOL CHILDREN - Kalmykova, Larysa; Kharchenko, Nataliia; Mysan, Inna; Rudkivska, Nataliia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Aim: to investigate the state of development of the operations to understand the grammatical meaning of phrases and its use in the speech of senior preschool children. Research procedure. The technique of “Comprehension of phrases” (Luria, 1998) was used to study the state of understanding by children of the grammatical meaning of different kinds of phrases. The state of the development in children of intra-speech operations related to semantic syntax and choice of linguistic meanings was investigated. The method of “Making up stories, descriptions, and reflections” was used to study the ability of children to use phrases in the process of constructing texts.Results. The multilevelled state of the development in children of the operations of understanding the meanings of phrases and its use in speech, which is conditionally fixed in the form of 4 levels: high, sufficient, medium, low was revealed. It is established that both the operations of understanding the grammatical meaning of phrases and the operations of the use of phrases in a verbal speech in senior preschoolers are at the stage of its development. It has been revealed that children understand much more grammatical meanings of phrases than they use in oral speech. The expression in a speech of the relationships existing in the real (surrounding) reality through phrases is a much more complicated speech operation for children than an understanding of the grammatical meanings of these phrases.